2008
DOI: 10.1038/nmat2114
|View full text |Cite
|
Sign up to set email alerts
|

Direct imaging of the spatial and energy distribution of nucleation centres in ferroelectric materials

Abstract: Macroscopic ferroelectric polarization switching, similar to other first-order phase transitions, is controlled by nucleation centres. Despite 50 years of extensive theoretical and experimental effort, the microstructural origins of the Landauer paradox, that is, the experimentally observed low values of coercive fields in ferroelectrics corresponding to implausibly large nucleation activation energies, are still a mystery. Here, we develop an approach to visualize the nucleation centres controlling polarizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
242
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 269 publications
(251 citation statements)
references
References 35 publications
8
242
1
Order By: Relevance
“…2b, a new À c-domain (where the negative sign indicates downward polarization) nucleates and grows at the top interface at a bias of 8.2 V, leading to the contrast change from bright to dark. Although previous studies proposed that the nucleation of c-domains preferentially begins from 90°domain walls 3,8,15 , our in situ TEM observations revealed that nucleation occurs only at the top interface with a negative bias 5,10 . The switched À c-domain grew with increasing voltage (Fig.…”
Section: Resultscontrasting
confidence: 91%
See 1 more Smart Citation
“…2b, a new À c-domain (where the negative sign indicates downward polarization) nucleates and grows at the top interface at a bias of 8.2 V, leading to the contrast change from bright to dark. Although previous studies proposed that the nucleation of c-domains preferentially begins from 90°domain walls 3,8,15 , our in situ TEM observations revealed that nucleation occurs only at the top interface with a negative bias 5,10 . The switched À c-domain grew with increasing voltage (Fig.…”
Section: Resultscontrasting
confidence: 91%
“…An understanding of the local response and underlying dynamic behaviour of individual domain walls and defects throughout the thickness of the film during the switching process is necessary, however, to engineer reliable ferroelectric devices [6][7][8][9][10][11][12][13][14] . This is especially important in ferroelectric memory devices scaled down to the nanometre scale to achieve a high data storage density where a single defect may dominate the total switching process.…”
mentioning
confidence: 99%
“…25,26 In perovskite oxides, it is known that mobile V O 2 þ ions tend to occupy thermodynamically preferential sites in extended crystal defects, such as DWs, grain boundaries and dislocations. [27][28][29][30][31][32][33][34] Often, these vacancies modify local cation valences and displacements and act as wall-pinning centers. 35 In turn, they contribute to diffusive photovoltaic switching in our multidomain BFO channels, as shown in Figures 5b and d.…”
Section: Resultsmentioning
confidence: 99%
“…There is a large amount of experimental evidence that both switching mechanisms are strongly affected by the defect structure of the ferroelectric medium. 3,4 Domain wall creep has been observed in the disordered systems with longrange variations in pinning potential (so-called random field disorder) with the wall velocity obeying an exponential field dependence, while the short-range (random bond) disorder leads to a power law dependence. 5,6 Dissimilar distribution functions of switching times in ferroelectric films with different microstructure are the root cause for qualitatively different time-dependent switching behavior described either by the statistical Kolmogorov−Avrami−Ishibashi model 7,8 or nucleation limited kinetics.…”
mentioning
confidence: 99%